Treatment-related early discontinuations and adverse events among newly diagnosed people living with HIV initiating integrase inhibitors in a real-world setting. Issue 2 (25th April 2023) - Rolle, Charlotte-Paige; Castano, Jamie; Nguyen, Vu; Patel, Kiran; Hinestrosa, Federico; DeJesus, Edwin
Background: Cohort studies suggest higher discontinuation rates with integrase strand transfer inhibitors (INSTIs) than are seen in clinical trials. We assessed discontinuations and adverse events (AEs) that were considered related to the initial INSTI in the first year following initiation among treatment-naïve people living with HIV (PLWH). Methods: Newly diagnosed PLWH initiating raltegravir, elvitegravir/cobicistat, dolutegravir or bictegravir in combination with emtricitabine/tenofovir alafenamide or emtricitabine/tenofovir disoproxil fumarate between 10/2007 and 1/2020 at the Orlando Immunology Center were included. Unadjusted incidence rates (IRs) and incidence rate ratios (IRRs) were calculated for treatment-related discontinuations and AEs associated with the initial INSTI in the first year following initiation. Results: Of 331 enrolled, 26 (8%) initiated raltegravir, 151 (46%) initiated elvitegravir/cobicistat, 74 (22%) initiated dolutegravir and 80 (24%) initiated bictegravir. Within the first year, treatment-related discontinuations occurred in 3 on elvitegravir/cobicistat (IR 0.02 per person-years (PPY)) and 5 on dolutegravir (IR 0.08 PPY); no treatment-related discontinuations occurred among those initiating raltegravir or bictegravir. Eleven treatment-related AEs occurred in 7 on raltegravir (IR 0.46 PPY), 100 treatment-related AEs occurred in 63 on elvitegravir/cobicistat (IR 0.72 PPY), 66 treatment-related AEs occurred in 37 on dolutegravir (IR 0.97 PPY) and 65 treatment-related AEs occurred in 34 on bictegravir (IR 0.88 PPY). Unadjusted IRRs did not reveal any significant difference between INSTIs in terms of early treatment-related discontinuations or AEs. Conclusions: In our cohort, treatment-related AEs occurred in 43% initiating INSTIs but were responsible for early discontinuation in only 2% with no treatment-related discontinuations observed among those initiating RAL or BIC.